Development of low-clinker concrete: partial replacement of cement with calcined clay and limestone, based on selected African raw materials - Leo, Emmanuel Safari (Department of Civil Engineering, 2023)
The most promising option for lowering the cost and environmental impact of cement is the use of blended cement. The well-known supplementary cementitious materials such as slag and fly ash are limited in most African countries. An attractive option is to produce LC3 binders, which consist of ground limestone, calcined kaolinite clay, and cement. In this study, the suitability of kaolinite clays for use in LC3 binders from selected deposits in South Africa and Tanzania was assessed. Four samples of clays were selected for the experimental work. The selection was based on the kaolinite content of the clay. Further, LC3 mixes with clinker content in the range of 40% to 70% were designed using the mixture design 3-factors approach. The compressive strength of mortar with a water/binder ratio of 0.4 was used as the performance parameter for optimising proportions. Two reference mixes were considered: a mix with 100% CEM II/A-L 52.5 N, and a recommended mix for South African marine environments with 50% cement replaced by ground-granulated blast-furnace slag. In general, the results suggest that, for optimum performance, regardless of the type of clay, the lowest practical clinker content is 55%, at which the amount of calcined clay is 35% and the amount of limestone is 10%. However, on the knowledge that high compressive strength does not automatically represent concrete with excellent durability, two other LC3 proportions were also considered for the concrete work: one with 65% clinker, 25% calcined clay and 10% limestone and the other with 45% clinker, 40% calcined clay and 15% limestone. The performance properties of the concrete mixes considered were workability, strength development, durability indexes, chloride diffusion characteristics, electrical resistivity, carbonation resistance, shrinkage, and potential for early age cracking. Overall, it can be concluded that the selected LC3 concrete mixes perform similarly or better than the reference mixes. The results indicate that, apart from kaolinite content, factors that influence the performance of the system include other minerals present in the clay, the filler effect, pozzolanic reaction, formation of carboaluminate phases, stabilisation of the ettringite phase, and the internal surface area of the clay.